Analisis Faktor yang Memengaruhi Kesempatan Kerja di Kota Jayapura - Setiawan, Tommy (Politeknik Statistika STIS, 2025)
Unemployment is a major issue currently faced by Jayapura Municipality. Population growth, along with labor migration from other regions, has contributed to a labor surplus in the city. This surplus has led companies to adopt specific criteria to screen prospective workers. Moreover, the significant influx of migrant workers into Jayapura has raised concerns about unequal employment opportunities for indigenous Papuans, as employers are feared to be more inclined to hire workers from outside the Papua region. This study aims to identify the factors that influence employment opportunities in Jayapura, using data from the August 2024 National Labor Force Survey (Sakernas) and applying a Binary Logistic Regression method. The results show that the variable 'Place of Birth' has a significant effect on employment opportunities in Jayapura, where workers born in Papua are less likely to be employed compared to those born outside Papua. In addition, variables such as Gender, Age, Disability Status, Marital Status, and Education Level also have a significant influence on employment opportunities. Meanwhile, training experience and the use of technology were found to have no significant effect on employment opportunities in the city.